2005
DOI: 10.1007/s00595-004-2888-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Iron Supplementation and Intraoperative Transfusion During Colorectal Cancer Surgery

Abstract: Iron supplementation for at least 2 weeks before colorectal cancer surgery increases Hb and Ht values in anemic patients, and reduces the need for intraoperative transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 15 publications
2
51
0
2
Order By: Relevance
“…our results attract notice to blood management measures, including correction of preoperative anemia by administration of iron, recombinant human erythropoietin, folic acid, and vitamin B 12 to avoid aBt. 8,[34][35][36][37][38] Preoperative correction of anemia by those measures could be an auspicious approach for future randomized trials. the application of low transfusion triggers where appropriate may be another approach.…”
Section: Discussionmentioning
confidence: 99%
“…our results attract notice to blood management measures, including correction of preoperative anemia by administration of iron, recombinant human erythropoietin, folic acid, and vitamin B 12 to avoid aBt. 8,[34][35][36][37][38] Preoperative correction of anemia by those measures could be an auspicious approach for future randomized trials. the application of low transfusion triggers where appropriate may be another approach.…”
Section: Discussionmentioning
confidence: 99%
“…Only one observational study found oral iron was significantly more effective in patients with anaemia than no treatment. Okuyama et al studied 116 anaemic patients undergoing colorectal surgery with a mean age of 67 years [28]. Oral iron increased haemoglobin by 2 g/dL compared with 0.9 g/dL in the control group without iron (p \ 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…1). Nineteen studies were subsequently excluded as they compared different types of iron supplementation (N = 6) [15,[20][21][22][23][24], involved erythropoietin being simultaneously commenced (N = 3) [25][26][27], were observational studies only (N = 3) [7,28,29], compared groups with a mean age between 29 and 44 years [30,31], included non-anaemic participants (N = 2) [32,33], had no control or placebo group (N = 2) [34,35] or involved only participants between 40 and 55 years of age and no older people (N = 1) [36]. Therefore, only three studies were included in the full review ( Fig.…”
Section: Literature Search and Trial Flowmentioning
confidence: 99%
“…Two similar studies have previously been conducted. Okuyama et al 11 identified 116 anaemic patients from a cohort of 569, 32 of whom received iron supplementation and the remaining 84 did not. The iron group were less likely to require an intra-operative transfusion.…”
Section: Discussionmentioning
confidence: 99%